Determination of methane emissions in three hydroelectric dams in Costa Rica - Herrera, Jorge (2013)
The emission fluxes of methane (CH4) across air–water interface were measured in three hydroelectric dams in Costa Rica (Brasil, Nuestro Amo and Cote Lake) during three years cycle (2009-2011), using the floating static chamber technique. Samples were taken during one week, both day and night time, through four campaigns per year. For the methane flux determination the water surface was divided in a 4x4 grid equally spaced. During this period, CH4 fluxes showed average values that ranged from 759 – 4282 (Brasil), 77 – 733 (Nuestro Amo) and 10,9 – 44,2 mg CH4 m-2 d-1 (Cote Lake), respectively. The fluxes of CH4 showed both strong seasonal and diurnal variations. CH4 emission rate was highest in dry season and there was a significant difference for CH4 emissions between day and night, the ratios between nighttime to daytime methane flux increased from 0,35 to 0,72, 0,43 to 0,64 for Brasil and Nuestro Amo, respectively in this season. CH4 emission was correlated positively with soil temperature, water table and chlorophyll a water concentrations.